Study on the environmental adaptation characteristics of red panda release into the wild - Yanshan Zhou; Chao Chen; Xiang Yu; Wenlei Bi; Rui Ma; Wei Wu; Jiabin Liu; Guanwei Lan; Haijun Gu; Qian Zhang; Kunlin Yang; Liqiang Fu; et al. (PLoS ONE, 2025)
Animals undergo a cognitive process when exposed to novel environments, which plays a crucial role in their ability to identify optimal habitats and support long-term survival. We conducted an initial investigation into the spatial utilization and habitat selection patterns of a femal red panda using GPS collar technology. Our research revealed that the home range and core activity area of the red panda was larger during initial 60 days after release, and markedly decreased thereafter. The red panda’s selection of altitude did not align with that of wild individuals until 60 days after release, whereas slope selection may require at least 30 days to stabilize and become consistent with wild individuals’ patterns. Our study further revealed that the home range and core activity area of the red panda showed low overlap with the suitable habitat of the wild population during the initial two months; however, this overlap increased significantly, reaching over 90% thereafter. We hypothesize that the red panda may require at least 60 days to acclimate to its new environment after release. Although our study was only based on a single individual, it provides the first evidence of the environmental adaptation process of red panda following released into the wild, thereby establishing a crucial foundation for future conservation and reintroduction initiatives.